A meta-analysis of serological response associated with yellow fever vaccination - Jean,K; Donnelly,C; Ferguson,N; Garske,T (American Journal of Tropical Medicine and Hygiene, 2016)
Despite previous evidence of high level of efficacy, no synthetic metric of yellow fever (YF) vaccine efficacy is currently available. Based on the studies identified in a recent systematic review, we conducted a random-effects meta-analysis of the serological response associated with YF vaccination. Eleven studies conducted between 1965 and 2011 representing 4,868 individual observations were included in the meta-analysis. The pooled estimate of serological response was 97.5% (95% confidence interval [CI] = 82.9–99.7%). There was evidence of between-study heterogeneity (I2 = 89.1%), but this heterogeneity did not appear to be related to study size, study design, seroconversion measurement, or definition. Pooled estimates were significantly higher (P & 0.0001) among studies conducted in nonendemic settings (98.9%, 95% CI = 98.2–99.4%) than among those conducted in endemic settings (94.2%, 95% CI = 83.8–98.1%). These results provide background information against which to evaluate the efficacy of fractional doses of YF vaccine that may be used in outbreak situations.